(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Putra FP, Kusmiyati F, Anwar S, Widaryati, Sas MGA. 2022. Variation in leaf characters and agronomical traits of Yard-long bean genotypes between Dimocarpus longan and Psidium guajava stand. Biodiversitas 23: 5752-5758. Yard-long bean (Vigna unguiculata subs. sesquipedalis) is one of the most familiar horticulture crops. Leaf characteristics such as trichomes, stomata, and chlorophyll content correlated to other traits that influenced tolerance under sub-optimum conditions and component production traits. This study aimed to evaluate the leaf characters and agronomical traits variations of the Yard-long bean genotypes. The study was conducted by Split-plot design, with the primary factor were shading between Psidium guajava and Dimocarpus longan Lour. stand. The sub-plot was seven genotypes of Yard-long beans. Analyses were performed of multiple components, including the density of trichome, density of stomata, chlorophylls, carotenoids, nitrate reductase activity, flowering times, harvesting times, and production components under shading conditions between D. longan and P. guajava stands. The density of trichome, density of stomata, total chlorophyll, carotenoid, and Nitrate reductase activity showed the variability responses for each genotype in different shading conditions. One genotype showed early flowering in shaded conditions between D. longan than in shaded conditions between P. guajava. Two genotypes have the potential to adapt under shade conditions between D. longan. The morpho-agronomic characters that have been characterized may be used as potential donors for future hybridization programs to develop superior yard-long bean varieties.